A virtual globe-based three-dimensional dynamic visualization method for gas diffusion. (January 2019) - Cheng, Ruozhen; Chen, Jing; Cao, Ming
Abstract : Three-dimensional dynamic visualization of the long range gas diffusion contributes to disaster forecasting and assessment. Existing three-dimensional visualization methods, which calculate the gas concentration without considering the terrain and display the gas concentration in the local range by isosurfaces, cannot meet the demand for intensive calculation and dynamic visualization of gas diffusion over a wide range. This study proposes a virtual globe-based three-dimensional dynamic visualization method of the long range gas diffusion, consisting of a voxel-based multi-scale data model, a terrain-dependent multi-scale concentration field calculation method using graphics processing units (GPU), and a GPU-based multi-scale spherical ray-casting algorithm. The method is then applied to the long range natural gas diffusion and is evaluated according to the efficiency of the concentration calculation and dynamic visualization. The results show that the proposed method can achieve dynamic visualization of the long range gas diffusion above 30 frames per second. Highlights: We present a virtual globe-based three-dimensional dynamic visualization method. It visualizes long range gas diffusions whilst considering terrain effects. Computing efficiency using GPU is approximately 15 times that using CPU. This method can achieve dynamic visualization above 30 frames per second and enable the prediction of gas leaks.